The Influence of Audio-Visual Media on Listening Skills and Writing Ability of Fifth Grade Elementary School Students in terms of Learning Independence - Anlianna (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2022)
The purpose of this research is a. The effect of audio-visual media on students' listening and writing skills, b. The effect of high and low learning independence of students when studying with audio-visual media on students' listening and writing skills, and c. The interaction between audio visual media and independent learning on students' listening and writing skills. The method used in this study is a quantitative approach with a quasi-experimental method using a 2 x 2 factorial research design. Researchers took samples using the saturated sample technique from the fift grade student population of SD Negeri 1 Kendari in the even semester of the 2020/2021 academic year. The sample used was 38 students who were divided into the experimental group and the control group. The results showed that there was a significant difference in the effect of audio-visual media and without audio-visual media on students' listening and writing skills, where the F value was 18.26 with a significant value of 0.00 less than 0. ,05; there is an effect of high and low learning independence of students when learning with audio-visual media on students' listening and writing skills, this is evidenced by looking at the F value of 4.50 with a significant value of 0.03 less than 0.05; there is an interaction between audio-visual and verbal media and learning independence on students' listening and writing skills, this is evidenced by the two-way ANOVA calculation, namely by looking at the F value of 4.02 with a significant value of 0.04 less than 0.05.